A quick RNA mini-prep for Neurospora mycelial cultures - K. M. LINDGREN; A. LICHENS-PARK; J. L. LOROS; J. C. DUNLAP (Fungal Genetics Reports, 1990)
Most RNA isolation techniques currently in use have been developed for the processing of large quantities of material. These typically involve multiple phenol extractions (Reinert et al. 1981 Mol. Cell Biol. 1:829-836) or guanadinium isothio-cyanate/cesium chloride gradients (Chirgwin et al. 1979 Biochem 18:5294-5299) and can be both expensive and time consuming. Often, however, needs arise where quantitatively smaller amounts of RNA are needed from many different samples, for example, during time series analyses or when screening transformants for expression of a transformed gene. Under such circumstances, existing techniques are overly time consuming and yield more RNA than is necessary. The availability of a rapid RNA mini-prep is thus desirable. Such a system has been developed for isolating plant RNA (Nagy et al. 1988 Plant Molecular Biology Manual, B4; ed. Gelvin and Schilperoort, Klewer Academic Publishing, pp. 1-29), and we have adapted this procedure for use with Neurospora and, potentially, other filamentous fungi. Below, we describe the use of this procedure with 50 ml mycelial cultures, although we have used in with equal success with 5 ml cultures without scaling down the amounts of any reagents.